Investigating the Insights of Nursing Students About Clinical Pharmacology Courses - Kiarash Fekri; Fereshteh Araghian Mojarad; Mehrrooz Alishah; Seyed Robabe Babaei; Tahereh Yaghoubi (Acta Medica Iranica)
Nursing education, requires critical attention to the science of pharmacology as well as employment of the relevant clinical skills. Therefore, the present study intends to investigate the insights of nursing students about clinical pharmacology courses. This cross-sectional descriptive study was performed on a community consisted of all nursing students who selected their clinical pharmacology course. The researcher-built questionnaire was the tool for collecting the data. Descriptive (percentage, mean and standard deviation) and analytical (t-test and Mann-Whitney non-parametric test) statistics were utilized to analyze the data using SPSS-22. The ethical considerations of the research were observed. Based on the findings, the variables of gender and the pharmacology grade achieved in the second semester predicted the level of satisfaction with clinical pharmacology course among the students as well as studying about the medicines before starting the internship. Regarding the relative satisfaction in this study, 85% of the students found the applications employed for learning clinical pharmacology contents effective to boost their skills and knowledge so that it would be recommended to use the novel educational methods for better learning of the course.